The Influence of Academic Supervision and Professional Learning Community (PLC) on Teacher Professional Competency: Does the Mediation of Self-Confidence Matter? - Andreas Fredyansa Harwisaputra; Athok Fu’adi; Rihab Wit Daryono (South Sulawesi Education Development (SSED), 2024)
This research explores self-confidence's role as a mediator in the influence between academic supervision, the Professional Learning Community (PLC), and teacher professional competence. The survey method was used to collect data based on purposive sampling from 60 teachers at SMAN 2 Ponorogo who were involved in the PLC program. Data collection was carried out using a questionnaire consisting of a Likert scale with 4 alternative answers. PLS-SEM analysis was used to analyze data and test the conceptual model. The results of the analysis show that academic supervision does not have a significant effect on teachers' self-confidence and professional competence. In addition, self-confidence was proven not to mediate the influence between academic supervision and PLC professionalism on teacher professional competence. These findings highlight the importance of self-confidence in facilitating the development of teachers' professional competence through academic supervision and participation in learning communities. The practical implication of this research is the need for a holistic approach to teacher development, which does not only focus on the technical aspects of expertise but also psychological aspects such as self-confidence. Research supports efforts to design professional development programs that strengthen teachers' self-confidence and integrate academic supervision and PLC professionalism to enhance their professional competence